Assessing The Characteristics of Coastal Neighbourhoods That Influence Flood Susceptibility in Kosofe, Nigeria - Ajijola, Saudat O; Adedire, Funmilayo M; Fadamiro, J A (CSID Journal of Infrastructure Development, 2024)
As climate change continues to exacerbate weather patterns, flood susceptibility has become an increasingly pressing global concern. The susceptibility to floods is influenced by many contextual factors; as such, characterizing coastal neighbourhoods for the purpose of articulating susceptibility pathways is crucial for developing appropriate physical planning policies. The specific research objective seeks to assess the dimensions of neighbourhood characteristics that influence flood susceptibility in Kosofe, a suburban coastal community in Lagos, Nigeria. The data used were based on primary and secondary sources. Using a systematic sampling method, 324 respondents participated in the field survey. The result of the descriptive statistics, as reflected in the moderate (3.32) to low mean value (1.54) from the highest to the least ranked features, showed some level of inadequacies with the overall quality of the neighbourhood. Also, the outcome of the factor analysis identified two dimensions of neighbourhood characteristics in the study area: spatial configuration and amenities. Further analyses showed that the factors that significantly influence flood susceptibility within Kosofe are embedded within its spatial configuration. This implies that the layout of various physical attributes and features of coastal neighbourhoods has important implications for flood risk reduction. Considering features such as natural open spaces, flood gardens, drainage systems, waste management infrastructure, water supply, roads and street networks, flood barriers, and warning systems are vital in spatial planning to minimize flood susceptibility and enhance resilience in coastal neighbourhoods.